2021
DOI: 10.3389/fmolb.2020.555630
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Germline Background of Single and Multiple Primary Melanomas

Abstract: Background: Melanoma has a complex molecular background and multiple genes are involved in its development and progression. The advent of next generation sequencing platforms has enabled the evaluation of multiple genes at a time, thus unraveling new insights into the genetics of melanoma. We investigated a set of germline mutations able to discriminate the development of multiple primary melanomas (MPM) vs. single site primary melanomas (SPM) using a targeted next generation sequencing panel.Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A study of multiple biological pathways showed that single nucleotide polymorphisms (SNPs) near CYP1B1, which is a nevus gene, reached global significance in a bivariate analysis examining melanoma risk (18). Recent research has shown that certain germline mutations, such as CYP1B1, may contribute to the differential development of melanoma susceptibility (19). In 2016, Sumantran et al reported that CYP1B1, which metabolizes most anti-cancer drugs, was more downregulated in melanoma samples than normal skin samples.…”
Section: Discussionmentioning
confidence: 99%
“…A study of multiple biological pathways showed that single nucleotide polymorphisms (SNPs) near CYP1B1, which is a nevus gene, reached global significance in a bivariate analysis examining melanoma risk (18). Recent research has shown that certain germline mutations, such as CYP1B1, may contribute to the differential development of melanoma susceptibility (19). In 2016, Sumantran et al reported that CYP1B1, which metabolizes most anti-cancer drugs, was more downregulated in melanoma samples than normal skin samples.…”
Section: Discussionmentioning
confidence: 99%
“…Each sequencing sample was loaded on an Ion 318 Chip Kit v2 BC (Thermo Fisher Scientific, Waltham, MA, USA) and sequenced on an Ion Torrent Personal Genome Machine (PGM) (Thermo Fisher Scientific, Waltham, MA, USA) for 1250 flows using an Ion PGM Hi Q Sequencing Kit (Thermo Fisher Scientific, Waltham, MA, USA) [ 13 ]. The Ion Torrent PGM was used along with the specific pipeline software Torrent Suite v 5.0 (Thermo Fisher Scientific, Waltham, MA, USA) to generate sequence reads, trim adapter sequences, and filter and remove poor-signal profile reads from the sequencing data [ 14 ]. The primer-trimmed files were then imported into Quantitative Insights Into Microbial Ecology 2 (QIIME2) v. 2020.11 software [ 15 , 16 ] for microbiota analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) and meta-analyses have widely demonstrated the association of RHC variants with increased risk of melanoma [ 124 , 138 , 139 , 140 , 141 ] and NMSCs [ 71 , 124 , 131 , 142 , 143 ]. These associations were initially related to the pigmentary functions of MC1R , although many studies confirmed that the increased skin cancer susceptibility in MC1R carriers is independent from pigmentary traits [ 28 , 71 , 144 , 145 , 146 ].…”
Section: Mc1r and Skin Cancers Riskmentioning
confidence: 99%
“…Germline MC1R variants may influence the mutational landscape of melanoma [ 146 , 156 ]. Despite the well-established impact of MC1R on skin cancer risk and development, the association of MC1R variants in combination with mutations in susceptible melanoma genes has not been clarified yet.…”
Section: Mc1r Association With Melanoma Susceptible Genesmentioning
confidence: 99%
See 1 more Smart Citation